Successful Urethrorectal Fistula Repair Using GelPOINT Path Anal Access Sheath in Pelvic Fracture Urethral Injury - Wataru Tanaka; Akihiro Kanematsu; Naohito Beppu; Kenichiro Kawai; Shinpei Yoshioka; Kimihiro Shimatani; Toeki Yanagi; Masao Kakibuchi; Masataka Ikeda; Shingo Yamamoto (IJU Case Reports, 2025)
ABSTRACT Introduction We present a case of rectourethral fistula complicating urethral trauma, successfully treated using a transanal exposure device. Case Presentation A male in his twenties was referred to us with a pelvic fracture urethral injury. Preoperative imaging revealed an urethrorectal fistula. Excision and primary anastomosis urethroplasty was performed transperineally. The fistula was primarily closed transanally via GelPOINT Path access sheath, which provided wide access to the anal canal. The closure was reinforced perineally, with a gracilis muscle flap interposition. Postoperative urethral patency was excellent without recurrent fistula. Conclusion This method could be an effective alternative for urethrorectal fistula repair.